Effect of Remoistening on The Chemical Composition, Fermentation Characteristics, and Ruminal Digestibility of Corn Silage - Paradhipta, Dimas Hand Vidya; Katon, Anas Dien; Hidayah, Kharisma Taufiqa; Agus, Ali; Astuti, Andriyani (Jurnal Ilmu-Ilmu Peternakan, 2025)
This study was conducted to determine the effects of remoistening on the chemical composition, fermentation characteristics, and ruminal digestibility of corn silage. Corn forage was harvested at the ½ milking stage containing 35% dry matter (DM) and then fermented for 21 days without remoistening (CON) or with 3 days wilting then remoistening to reach the original DM (TRT). This study was conducted with 4 replications per treatment in a mini silo (3 kg) and analysed via the independent sample t test. Compared with those of the CON silage, the pH and ammonia content of the TRT silage were greater (p<0.001). Similarly, the lactic acid, acetic acid and butyric acid contents of the TRT silage were lower (p<0.001) than those of the CON silage. Compared with those of the CON silage, the chemical composition of the TRT silage after fermentation included lower DM, organic matter (OM), and crude protein contents (p<0.001). Poor-quality TRT silage reduced the in vitro DM digestibility and OM digestibility of corn silage.